2016
DOI: 10.1002/jms.3794
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous monitoring of monoamines, amino acids, nucleotides and neuropeptides by liquid chromatography-tandem mass spectrometry and its application to neurosecretion in bovine chromaffin cells

Abstract: The primary functions of adrenal medullary chromaffin cells are the synthesis and storage in their chromaffin vesicles of the catecholamines noradrenaline (NA) and adrenaline (AD), and their subsequent release into the bloodstream by Ca -dependent exocytosis under conditions of fear or stress (fight or flight response). Several monoamines, nucleotides and opiates, such as leucine-enkephalin (LENK) and methionine-enkephalin (MENK), are also co-stored and co-released with the catecholamines. However, other neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Therefore, this study developed targeted MS identification and quantitation of 14 classical neurotransmitters by GC-TOF (gas chromatography time-of-flight), combined with LC-MS/MS (liquid chromatography coupled to tandem mass spectrometry) analyses. GC-TOF is appropriate for analyses of low molecular weight molecules , but has not been used in prior neurotransmitter analyses, which have largely utilized LC-MS and LC-MS/MS. . Results of this study found that GC-TOF, combined with LC-MS/MS, provides an improved metabolomics strategy for analyses of 14 classical neurotransmitters consisting of acetylcholine, adenosine, anandamide, aspartate, dopamine, epinephrine, GABA, glutamate, glycine, histamine, melatonin, norepinephrine, serine, and serotonin.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, this study developed targeted MS identification and quantitation of 14 classical neurotransmitters by GC-TOF (gas chromatography time-of-flight), combined with LC-MS/MS (liquid chromatography coupled to tandem mass spectrometry) analyses. GC-TOF is appropriate for analyses of low molecular weight molecules , but has not been used in prior neurotransmitter analyses, which have largely utilized LC-MS and LC-MS/MS. . Results of this study found that GC-TOF, combined with LC-MS/MS, provides an improved metabolomics strategy for analyses of 14 classical neurotransmitters consisting of acetylcholine, adenosine, anandamide, aspartate, dopamine, epinephrine, GABA, glutamate, glycine, histamine, melatonin, norepinephrine, serine, and serotonin.…”
Section: Introductionmentioning
confidence: 95%
“…However, to the best of our knowledge based on extensive literature evaluation, there are currently no publications that have reported identification and quantitation of the major spectrum of 14 classical neurotransmitters, as analyzed by this study. While many studies have conducted MS analyses of “neurotransmitters”, most have only analyzed 3–6 neurotransmitters and a few have analyzed 7–8 neurotransmitters. Many of these studies of “neurotransmitters” include metabolites, rather than only the bona fide neurotransmitters. For these reasons, there is a need to develop metabolomics methodology for quantitative profiling of the major repertoire of 14 classical neurotransmitter molecules, the goal of this study.…”
Section: Introductionmentioning
confidence: 99%
“…The supernatant was collected, centrifuged at 3000 rpm for 2 min at 4 • C (Eppendorf, Germany), and analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). A system consisting of a 1200 Series Liquid Chromatograph coupled to a 6410B Triple Quadrupole Mass Spectrometer (LC-MS; Agilent Technologies, Madrid, Spain) was used [57], and CAs were determined using a positive mode electrospray ionization; likewise, the pellet was analyzed for protein content.…”
Section: Adrenal Gland Samplesmentioning
confidence: 99%
“…The presence of 5-HT in adrenal glands has been demonstrated in various species including fish, frog, mouse, rat, pig, cattle and human [15][16][17][18][19][20][21]. The cell types that contain 5-HT differ among species.…”
Section: Occurrence Of 5-ht In Normal Adrenalmentioning
confidence: 99%